Интегрируемость уравнений Риккати и стационарные уравнения Кортевега-де Фриса - Жданов, Р.З. (Український математичний журнал, 1999)
За допомогою інфінітезимального методу С. Лі встановлено відповідність між інтегровністю однопараметричної сім'ї рівнянь Ріккаті та ієрархією вищих рівнянь Кортевега — де Фріса. By using the Lie infinitesimal method, we establish the correspondence between the integrability of a one-parameter family of Riccati equations and the hierarchy of the higher Korteweg-de Vries equations.